Leukoreduction system chambers are an efficient, valid, and economic source of functional monocyte-derived dendritic cells and lymphocytes - Pfeiffer, Isabell A.; Zinser, Elisabeth; Strasser, Erwin; Stein, Marcello F.; Dörrie, Jan; Schaft, Niels; Steinkasserer, Alexander; Knippertz, Ilka (Immunobiology, 2013)
The demand for human monocyte-derived dendritic cells (moDCs), as well as for primary human B and T lymphocytes for immunological research purposes has been increased in recent years. Classically, these monocytes are isolated from blood, leukapheresis products or buffy coats of healthy donors by plastic adherence of peripheral blood mononuclear cells (PBMCs), followed by stimulation with granulocyte macrophage colony-stimulating factor (GM-CSF) and interleukin (IL)-4, while lymphocytes are usually isolated from the non-adherent fraction (NAF) by magnetic cell sorting. However, donor-blood is a limited resource and not every blood bank offers leukapheresis products or buffy coats for laboratory use. Additionally, a leukapheresis is very expensive and also the generation/isolation of cells is time- and cost-intensive. To overcome some of these obstacles, we evaluated if low-cost leukoreduction system chambers (LRSCs), which arise after routine donor plateletpheresis procedures, and are usually discarded, would be an alternative and appropriate source of PBMCs to generate moDCs and to isolate lymphocytes. By analyzing the number and phenotype of immature and mature dendritic cells (DCs), as well as of B and T lymphocytes derived from LRSCs, we found all cells to be of high quantity and quality. Further investigations on DCs comprising transwell migration assays, allogeneic mixed lymphocyte reactions (MLR), cytokine secretion assays, and cytotoxic T cell induction assays revealed high migratory, as well as stimulatory capacity of these cells. In addition, DCs and T cells were efficiently electroporated with mRNA and showed characteristic cytokine production after co-culture, demonstrating LRSCs as an efficient, valid, and economic source for generation of moDCs and lymphocytes for research purposes. © 2013 Elsevier GmbH.
CRIS-Team Scopus Importer:2021-10-01
Keywords: B cell; Leukoreduction system chamber; Monocyte-derived dendritic cell; Peripheral blood mononuclear cell; T cell